Digital services in the development of tourism ("Journal "U". Economy. Management. Finance.", 2023)
The article analyzes the importance of digital services in the field of resort tourism in Russia, reveals the features of the development of digitalization of tourism in connection with the development of the global economy, determines the content and functionality of digital resources for the formation of competitive advantages of the resort and tourism sector at the municipal level.
Keywords: tourism; global economy; digital resources; national project; tourism product; aggregator services; digital portals